The Effect of Relevant and Irrelevant Humor in Educational Content on the Academic Engagement of Fourth-Grade Male Students - Tavakolian, Mehrzad; Asadzadeh, Hassan; Hosseini AlMadani, Seyed Ali; Shishvan, Ali Jalili (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The objective of this study was to investigate the impact of relevant and irrelevant humor in the science curriculum on the academic engagement of fourth-grade elementary school students. Methods and Materials: This study employed a quasi-experimental design with a multi-stage cluster sampling method. A total of 88 fourth-grade students from non-public schools in District 5 of Tehran participated in the study. Students were randomly assigned to three groups: the relevant humor intervention group, the irrelevant humor intervention group, and a control group. A humor-infused educational package combining relevant and irrelevant humor with science content was developed and implemented. Academic achievement was measured using a pre- and post-test design, and data were analyzed using analysis of covariance (ANCOVA). Findings: The findings indicated a significant difference in academic achievement between the relevant humor group and the control group, with the relevant humor group showing greater improvement in academic performance (p < 0.05). There was no significant difference between the irrelevant humor group and the control group (p > 0.05). The eta squared value of 0.14 indicated that 14% of the variance in academic achievement was explained by the humor interventions. Conclusion: The study concluded that incorporating relevant humor into the science curriculum can significantly enhance academic achievement by increasing student engagement, motivation, and understanding of the material. In contrast, irrelevant humor did not yield significant academic benefits, suggesting the importance of aligning humor with the curriculum content. Future research is needed to explore the long-term effects and broader impacts of humor interventions in education.